1981
DOI: 10.1039/f19817700427
|View full text |Cite
|
Sign up to set email alerts
|

Comparative adsorption of H2S, CH3SH and (CH3)2S on alumina. Structure of species and adsorption sites

Abstract: Structure et RCactivitk d'espkces adsorbees,' ERA 824 -I.S.M.R.A.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
29
1

Year Published

1997
1997
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(35 citation statements)
references
References 0 publications
5
29
1
Order By: Relevance
“…In the catalytic reactions of hydrogen sulfide oxidation [12,18,20] and decomposition [65], adsorption of H2S on the catalyst surface is thought to be necessary for H2S activation and its transformation to sulfide or sulfite/sulfate complexes [62,66]. Although H2S adsorption on -Al2O3 has been studied in detail [62,[66][67][68], there are debates concerning the nature of the sites involved in H2S adsorption. H2S adsorbs in molecular form on proton sites of -Al2O3 [62,67].…”
Section: Study Of Hydrogen Sulfide Adsorptionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the catalytic reactions of hydrogen sulfide oxidation [12,18,20] and decomposition [65], adsorption of H2S on the catalyst surface is thought to be necessary for H2S activation and its transformation to sulfide or sulfite/sulfate complexes [62,66]. Although H2S adsorption on -Al2O3 has been studied in detail [62,[66][67][68], there are debates concerning the nature of the sites involved in H2S adsorption. H2S adsorbs in molecular form on proton sites of -Al2O3 [62,67].…”
Section: Study Of Hydrogen Sulfide Adsorptionmentioning
confidence: 99%
“…The bridging lattice oxygen of the catalyst or oxygen adsorbed on the surface is consumed in H2S oxidation [71]. However, oxidation on -Al2O3 is hindered by the low mobility of surface oxygen [68]. Fig.…”
Section: Study Of Hydrogen Sulfide Adsorptionmentioning
confidence: 99%
“…5). By comparison with literature data the three high frequency bands are respectively ascribed to ν a (CH 3 ), ν s (CH 3 ), and 2δ a (CH 3 ) vibrations while the band at 2590 cm −1 corresponds to the ν(SH) stretching mode whose wavenumber is very close to that of the free molecule (40,41). In parallel, a strong decrease of the intensity of the 3740 cm −1 band characterizing SiO-H stretching mode is observed and a broad band at 3475 cm −1 assigned to perturbed SiO-H vibrations appears.…”
Section: Ch 3 Sh Adsorptionmentioning
confidence: 93%
“…[1][2][3][4] It is a prerequisite to reduce the H 2 S content from these streams to a low level as H 2 S is extremely malodorous and toxic, being the source of acid rain, causing pipeline corrosion and limiting plant lifetime, 5,6 as well as poisoning most downstream catalysts. 15,16 g-Al 2 O 3 has been widely used in industrial elds, as a catalyst support or as a catalyst (for the Claus process), 17 with inevitable reaction with H 2 S in potential suldation environments. 15,16 g-Al 2 O 3 has been widely used in industrial elds, as a catalyst support or as a catalyst (for the Claus process), 17 with inevitable reaction with H 2 S in potential suldation environments.…”
Section: Introductionmentioning
confidence: 99%
“…15,16 g-Al 2 O 3 has been widely used in industrial elds, as a catalyst support or as a catalyst (for the Claus process), 17 with inevitable reaction with H 2 S in potential suldation environments. 15,[20][21][22][23][24] For example, Travert et al studied interaction of H 2 S on g-Al 2 O 3 surface using infrared (IR) spectroscopy, 25 and showed that the adsorption of H 2 S irreversibly perturbs the high-frequency region of the IR spectroscopy and results in changes to surface acidity. Many attempts have been made to investigate the interaction mechanism of H 2 S with g-Al 2 O 3 , with adsorption of H 2 S on g-Al 2 O 3 surface studied using many instruments.…”
Section: Introductionmentioning
confidence: 99%